EXTREME SIGNIFICANT WAVE HEIGHT OF WESTERN AND CENTRAL INDONESIAN SEAS AND ITS CORRELATION WITH ISO 19901-1:2015 - Wurjanto, Andojo; Mukhti, Julfikhsan Ahmad; Wirasti, Hijir Della; Widyanintias, Yosinta Eka (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Extreme significant wave height is a commonly used parameter for designing offshore structures. ISO provides general extreme significant wave height information of six ocean regions in the world, including the Southern East Asian Sea. However, for the case of Indonesia, ISO only includes the Natuna Sea region. One of the qualified datasets that provide significant wave height data for Indonesian seas is SEAFINE by Oceanweather, Inc. This dataset covers the western and middle part of Indonesia. We analyzed the SEAFINE significant wave height hindcast data in these regions to obtain the extreme values. Extreme significant wave height maps were then produced based on the analyzed data. For the purpose of validation, we compared the extreme value analysis result with ISO 19901-1:2015 in regions where SEAFINE and ISO data intersect. The comparison showed that the analysis result tends to give approximately 25% lower wave height for a 1-year return period compared to ISO 19901-1:2015 but agreement for a 100-year return period. The SEAFINE analysis result also shows agreement with previous studies in the Karimata Strait and the Java Sea.